2009
DOI: 10.1111/j.1759-5436.2009.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for Nutrition Results in ICDS: Translating Vision into Action

Abstract: This article focuses on the Integrated Child Development Services (ICDS), India's largest nutrition and early child development programme. It describes the political, organisational and technical challenges to building and sustaining an outcomes-oriented approach to nutrition monitoring in India. We show that the environment is conducive to strengthening nutrition programme monitoring and evaluation. Political commitment is growing, financial allocations have increased and there have been a number of reforms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, several reviews and evaluations of ICDS over the past 18 years have also found persistent gaps, including inadequate infrastructure at the AWC, Anganwadi worker (AWW) service delivery issues (eg, poor quality supplementary food, few home visits and no counselling etc), human resource issues (eg, vacancies, increasing range of duties expected of the AWWs, inadequate training of AWWs, limited supervision etc) and poor data management (eg, irregularities in record keeping at AWCs, ineffective monitoring of service delivery etc) 3 4 9–11. The most recent NFHS (2015–206) also highlights the gaps in ICDS service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, several reviews and evaluations of ICDS over the past 18 years have also found persistent gaps, including inadequate infrastructure at the AWC, Anganwadi worker (AWW) service delivery issues (eg, poor quality supplementary food, few home visits and no counselling etc), human resource issues (eg, vacancies, increasing range of duties expected of the AWWs, inadequate training of AWWs, limited supervision etc) and poor data management (eg, irregularities in record keeping at AWCs, ineffective monitoring of service delivery etc) 3 4 9–11. The most recent NFHS (2015–206) also highlights the gaps in ICDS service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…(7) At the planning level, all nutrition items (supplies, training, human resources, cadre, monitoring and research) are not/inadequately budgeted for in the annual health budget plans ( Tsofa et al , 2021 ; Saini et al , 2022 ). (8) At reporting and review level, a consensus on which critical nutrition indicators to include is either unavailable or often lacking, even in recording registers and reporting, and as a result this is never reviewed ( Adhikari and Bredenkamp, 2009 ). (9) Maternal nutrition rapid assessment questions are missed when antenatal care (ANC) rapid assessments are carried out.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Levinson and Madzorera (2005) in their study on the monitoring and evaluation of nutrition-related projects in nine developing countries including India, remarked that in most of the nutrition project-related M & E the 'behavioural outcome' column was often neglected (Levinson & Madzorera, 2005). In addition, as nutritional deprivation is the effect of multiple factors from poverty to poor education to gender and attributing the change in the nutritional status to impact of a single programme may not give the correct picture (Adhikari & Bredenkamp, 2009). In addition, Levinson and Madzorera believe that the current system neglects the primary purpose of monitoring, that is, the ability to quickly correct the problems in implementation.…”
mentioning
confidence: 99%